Increasing surface charge density induces interdigitation in vesicles of cationic amphiphile and phosphatidylcholine - Ryhänen, Samppa J (Langmuir : the ACS journal of surfaces and colloids, 2005)
Binary vesicles of cationic lipid dihexadecyldimethylammoniumbromide (DHAB) and 1,2-dimyristoyl-sn-glycero-3-phosphocholine (DMPC) were examined by differential scanning calorimetry, fluorescence spectroscopy, and Fourier transform infrared spectroscopy. DHAB/DMPC vesicles demonstrate a complex dependence of the main-transition temperature (T(m)) on their mole proportion of DHAB, with a maximum of 42 degrees C at X(DHAB) = 0.4. An increase of T(m) at X(DHAB) < 0.4 is explained by reorientation of P(-)-N(+) dipoles of the phosphocholine headgroup, resulting in tighter packing of the acyl chains, which increases the thermal energy required for trans --> gauche isomerization. At X(DHAB) > 0.4, Coulombic repulsion between the cationic DHAB headgroups expands the bilayer evident as a decrease in T(m) until a plateau of approximately 28 degrees C at 0.7 < or = X(DHAB) > or = 0.9 is reached, followed by an increment of T(m) to approximately 30 degrees C at X(DHAB) > 0.9. The quenching of DPH-PC fluorescence emission and the decrease in the ratio of peak height intensities of symmetric and antisymmetric -CH(2)- stretching modes suggest an interdigitated phase to form at X(DHAB) > 0.6. Interdigitation allows the membrane to accommodate the augmented Coulombic repulsion between DHAB headgroups because of increasing cationic surface charge density while simultaneously causing tighter packing of the acyl chains evident first as a plateau at 0.7 < or = X(DHAB) > or = 0.9 and subsequently as an increase in T(m) at X(DHAB) > 0.9. Screening of the membrane charges by NaCl abolishes the quenching of DPH emission and decreases T(m), thus revealing electrostatic repulsion as the driving force for interdigitation